2017
DOI: 10.1016/j.ssresearch.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Applying to college: Do information deficits lower the likelihood of college-eligible students from less-privileged families to pursue their college intentions?

Abstract: Information deficits are considered an important source of why students from less-privileged families do not enroll in college, even when they are college-eligible and intend to go to college. In this paper, we examine whether correct and detailed information on the costs of and returns to higher education increases the likelihood of college applications of less-privileged high school graduates who expressed college intentions in their junior high school year. We employ an experimental design with a randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 66 publications
2
29
0
12
Order By: Relevance
“…However, there is also evidence that information interventions are efficient in changing beliefs about cost or returns from higher education and intentions to attend (Bleemer & Zafar, 2018;Oreopoulos & Dunn, 2012;Peter & Zambre, 2017). One study found that providing additional information about grants did not change college intentions but did increase college application behaviors (Ehlert, Finger, Rusconi, & Solga, 2017). Finally, providing general information about a prestigious grant changed disadvantaged students' knowledge but did not affect their propensity to apply to it, unless general information was combined with a meaningful role model who could show that someone with a similar background had been successful in obtaining such grants (Herber, 2018).…”
Section: Graduationmentioning
confidence: 99%
“…However, there is also evidence that information interventions are efficient in changing beliefs about cost or returns from higher education and intentions to attend (Bleemer & Zafar, 2018;Oreopoulos & Dunn, 2012;Peter & Zambre, 2017). One study found that providing additional information about grants did not change college intentions but did increase college application behaviors (Ehlert, Finger, Rusconi, & Solga, 2017). Finally, providing general information about a prestigious grant changed disadvantaged students' knowledge but did not affect their propensity to apply to it, unless general information was combined with a meaningful role model who could show that someone with a similar background had been successful in obtaining such grants (Herber, 2018).…”
Section: Graduationmentioning
confidence: 99%
“…Still, Peter and Zambre (2017) found that an information intervention in the form of a 20-min presentation increased college enrollment intentions by 8% two to three months later for students in non-academic families (i.e., first-generation students); intention persisted after one year, suggesting that exposing students to information may impact their decision-making. Similar studies (Ehlert et al 2017;Herber 2018;Macqueen 2017) showed information interventions contributed to prospective students' decision to enroll and improvement of students' knowledge base, particularly among those with lower socioeconomic backgrounds. However, there is great variance among the type of information, the mode of presentation, duration, and level of interaction across studies to determine the most effective method of information intervention.…”
Section: Discussionmentioning
confidence: 71%
“…However, there is also evidence that information interventions are efficient in changing beliefs about cost or returns from higher education and intentions to attend (Bleemer & Zafar, 2018;Oreopoulos & Dunn, 2012;Peter & Zambre, 2017). One study found that providing additional information about grants did not change college intentions but did increase college application behaviors (Ehlert, Finger, Rusconi, & Solga, 2017). Finally, providing general information about a prestigious grant changed disadvantaged students' knowledge but did not affect their propensity to apply to it, unless general information was combined with a meaningful role model who could show that someone with a similar background had been successful in obtaining such grants (Herber, 2018).…”
Section: Figure 2: Selected Estimates For the Impact Of Outreach On Amentioning
confidence: 99%